Situational strategic awareness monitoring surveillance system (SSAMSS) - Maldonado, Kenly R., author; Simske, Steven J., advisor; Miller, Erika, committee member; Herber, Daniel, committee member; Dandy, David, committee member (Colorado State University. Libraries, 2023)
This dissertation takes a Systems Engineering approach for the development of a cost-effective, deployable remote sensing materials safeguarding system. This co-called system-of-systems undergoes the major portions of the Systems Engineering development process to assure with confidence that a Situational Strategic Awareness Monitoring Surveillance System (SSAMSS) is a competitive product considered for actual development. The overall assessment takes a strategic approach by using selective tools to create, confirm and consider whether SSAMSS as a product idea ultimately should be developed into an actual prototypical Model (Engineering Model). Although the dissertation explores whether a prototype should be considerate with confidence and risk consideration it does not actually dive into the physical development of the model due to limited time and actual funding. Through the Systems Engineering V-Model, SSAMSS as a product and enterprise is vetted from the customer needs analyses through unit testing (the bottom of the V-model). This is the point where an actual customer would decide to continue the to incorporate SSAMSS into integration and testing, prototype to operations, maintenance, and retirement. Through simulations, assessment, and analysis it has been determined that SSAMSS as a product and enterprise is a viable option to supersede current material safeguarding systems that are competitive in the marketplace today.
Keywords: SSAMSS; remote sensing; systems engineering